2008
DOI: 10.1523/jneurosci.5382-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Differences in Expression of Histone DemethylasesUtxandUtyin Mouse Brain and Neurons

Abstract: Although X inactivation is thought to balance gene expression between the sexes, some genes escape inactivation, potentially contributing to differences between males and females. Utx (ubiquitously transcribed tetratricopeptide repeat gene on X chromosome) is an escapee gene that encodes a demethylase specific for lysine 27 of histone H3, a mark of repressed chromatin. We found Utx to be expressed higher in females than in males in developing and adult brains and in adult liver. XX mice had a higher level of U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
124
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(137 citation statements)
references
References 39 publications
9
124
0
Order By: Relevance
“…Moreover, although UTX is considered to escape X chromosome inactivation (45), we did not detect a difference in podocyte UTX levels between male and female patients. This observation is consistent with an earlier report that UTX expression from the inactive X chromosome is significantly lower than it is from the active X chromosome (46). Although UTX and Jmjd3 are similar in their JmjC catalytic domains, they are also structurally distinct.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, although UTX is considered to escape X chromosome inactivation (45), we did not detect a difference in podocyte UTX levels between male and female patients. This observation is consistent with an earlier report that UTX expression from the inactive X chromosome is significantly lower than it is from the active X chromosome (46). Although UTX and Jmjd3 are similar in their JmjC catalytic domains, they are also structurally distinct.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies demonstrated that UTX can escape chromosome X-inactivation in normal female tissues, 23,37,38 and accordingly, shows higher expression in female embryonic stem cells and female tissues derived from brain, liver, neurons, and sexual organs in comparison with their male counterpart. [36][37][38] The fact that UTX escapes chromosome X-inactivation in normal cells has important implications for gender-related tumor susceptibility. Indeed, given the previously established role for UTX as a tumor suppressor in human cancer, inactivation of only one single UTX copy in males will contribute to tumor development.…”
Section: Discussionmentioning
confidence: 97%
“…These receptors in turn influence gene expression by acting in complexes with co-activators and co-repressors, several of which have enzymatic activities modifying histones status [28]. Interestingly, both histone-acetylation and methylation are sexually dimorphic in the developing cortex and hippocampus of the mouse during the first post-natal week [29].…”
Section: Discussionmentioning
confidence: 99%